The Composition operator on hardy space H2 Induced by ?(z)=sz+t where , and (Baghdad Science Journal, 2025)
We study in this paper the composition operator of induced by the function ?(z)=sz+t where , and We characterize the normal composition operator C? on Hardy space H2 and other related classes of operators. In addition to that we study the essential normality of C? and give some other partial results which are new to the best of our knowledge.